BUSINESS OWNERSHIP AND RELIGIOUS IDENTITY IN A MUSLIM-MAJORITY COUNTRY: THE CASE OF DISPLAYING ISLAMIC IMAGES IN MALAYSIAN RESTAURANTS - Madun, Azian; Kamarulzaman, Yusniza (Online Journal of Islamic Management and Finance (OJIMF), 2023)
In a predominantly Muslim nation such as Malaysia, where halal cuisine is widely available, displaying Islamic images in restaurants may seem trivial. Nonetheless, this study reveals that there are meaningful interactions between ownership, religion, and the display of Islamic images in Malaysian restaurants. Using a structured observation method on a sample of 56 Malaysian restaurants that Muslims frequented, the authors examined the placing of Islamic images as wall decorations. This study found that privately held Muslim restaurants are more likely to display Islamic images, particularly those owned by Indian-Muslims. Restaurants owned by non-Muslims or international organisations, on the other hand, retain their neutrality by not exhibiting any religious symbols, despite the fact that some of them have halal certificates. The findings indicate that the behaviour of establishments owned by Muslims is consistent with their religious beliefs and the social identity of a majority-Muslim country. As for businesses owned by non-Muslims or multinational corporations, their religious neutrality is consistent with social identity theory, which aims to prevent confusion or hostility among Muslims towards these businesses. This study implicates that successful businesses employ practises that are easily relatable to consumers, such as displaying images that match with their beliefs. Therefore, businesses must make strategic adjustments to the social identity of the majority in order to prevent confrontations that would severely harm their brands.